Cytogenetic analysis of three sea catfish species (Teleostei, Siluriformes, Ariidae) with the first report of Ag-NOR in this fish family - Nirchio,Mauro (2010)
Despite their ecological and economical importance, fishes of the family Ariidae are still genetically and cytogenetically poorly studied. Among the 133 known species of ariids, only eight have been karyotyped. Cytogenetic analyses performed on Genidens barbus and Sciades herzbergii revealed that both species have 2n = 56 chromosomes and Cathorops aff. mapale has 2n = 52 chromosomes: Genidens barbus has 10 Metacentrics (M), 14 Submetacentrics (SM), 26 Subtelocentrics (ST), and 6 Acrocentrics (A), Sciades herzbergii has 14M, 20SM, 18ST and 4A, whereas Cathorops aff. mapale has 14M, 20SM, and 18ST. The nucleolus organizer regions (NORs) were found in a single chromosome pair on the short arm of a large-sized ST pair in Genidens barbus and on the short arm of a middle-size SM pair in Cathorops aff. mapale. Multiple NORs on the short arms of two large-sized ST pairs were found in Sciades herzbergii. The occurrence of diploid numbers ranging from 2n = 52 through 56 chromosomes and the presence of different karyotypic compositions, besides the number and position of NORs suggest that several numeric and structural chromosome rearrangements were fixed during the evolutionary history of this fish family.